On "Minimal Model Explanations": A Reply to Batterman and Rice. Issue 2 (April 2015) - Lange, Marc
Abstract : Batterman and Rice offer an account of "minimal model explanations" and argue against "common features accounts" of those explanations. This paper offers some objections to their proposals and arguments. It argues that their proposal cannot account for the apparent explanatory asymmetry of minimal model explanations. It argues that their account threatens ultimately to collapse into a "common features account." Finally, it argues against their motivation for thinking that an explanation appealing to "common features" would have to explain the common features' own prevalence.